Effect of sesamin against cytokine production from influenza type A H1N1-induced peripheral blood mononuclear cells: computational and experimental studies - Kanda Fanhchaksai (2018)
© 2015, The Society for In Vitro Biology. In 2009, swine flu (H1N1) had spread significantly to levels that threatened pandemic influenza. There have been many treatments that have arisen for patients since the WHO first reported the disease. Although some progress in controlling influenza has taken place during the last few years, the disease is not yet under control. The development of new and less expensive anti-influenza drugs is still needed. Here, we show that sesamin from the seeds of the Thai medicinal plant Sesamum indicum has anti-inflammatory cytokines in human peripheral blood mononuclear cells (PBMCs) induced by 2009 influenza virus type A H1N1. In this study, the combinatorial screening method combined with the computational approach was applied to investigate the new molecular binding structures of sesamin against the 2009 influenza virus type A H1N1 (p09N1) crystallized structure. Experimental methods were applied to propose the mechanisms of sesamin against cytokine production from H1N1-induced human PBMC model. The molecular dynamics simulation of sesamin binding with the p09N1 crystallized structure showed new molecular binding structures at ARG118, ILE222, ARG224, and TYR406, and it has been proposed that sesamin could potentially be used to produce anti-H1N1 compounds. Furthermore, the mechanisms of sesamin against cytokine production from influenza type A H1N1-induced PBMCs by ELISA and signaling transduction showed that sesamin exhibits the ability to inhibit proinflammatory cytokines, IL-1β and TNF-α, and to enhance the activity of the immune cell cytokine IL-2 via downregulating the phosphorylated JNK, p38, and ERK1/2 MAPK signaling pathways. This information might very well be useful in the prevention and treatment of immune-induced inflammatory disorders.